TRADITIONS AND MODERNITY CONFLICT IN UZBEK AND WESTERN LITERATURE - Matniyazova Ikboloy, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract. This article explores how the conflict between inherited tradition and disruptive modernity becomes a major engine of plot, character formation, and ethical debate in Uzbek and Western literary texts. Using Uzbek Jadid-era prose as a cultural “laboratory” of social change and comparing it with European modern drama and Anglo-Irish modernist fiction, the study shows that tradition is rarely a simple “enemy,” and modernity is rarely a clean “solution.” Instead, writers stage modernity as an experience of acceleration, uncertainty, and moral risk, while tradition functions as both shelter and constraint.